Alternatif Penyelesaian Sengketa pada Perkara Kewarisan: Analisis Hukum Islam dan Hukum Positif - Gulo, Azhar Nur Mawaddah; Harahap , Mhd. Yadi; Mukhsin, Abd. (Rayah Al-Islam, 2026)
Disputes over the distribution of inheritances and the determination of heirs in Indonesia often trigger protracted family conflicts due to legal pluralism, differing interpretations of inheritance provisions, and conflicting economic interests among heirs. Resolution through litigation is often time-consuming, costly, and has the potential to worsen family relationships. Previous research has generally addressed the resolution of inheritance disputes from the perspective of litigation or normative studies of inheritance law, whereas research examining the effectiveness of Alternative Dispute Resolution (ADR) in an integrated manner based on Islamic law and positive law remains relatively limited. This study aims to analyze the effectiveness and obstacles to the implementation of ADR in resolving inheritance disputes. This study employs a juridical-normative method with a legislative and conceptual approach through a literature review, while data are analyzed using content analysis. The results of the study indicate that mediation, negotiation, and conciliation are effective mechanisms because they prioritize deliberation, the principle of kinship, time and cost efficiency, and are in line with the principle of islah in Islamic law. However, its implementation still faces obstacles in the form of a lack of good faith among the parties, the dominance of personal interests, intervention by family members or legal representatives, limitations in mediators’ competence, and the fact that the legal force of out-of-court settlements is not yet optimal. The novelty of this study lies in its comparative and integrative analysis of the application of APS from the perspectives of Islamic law and Indonesian positive law. This study makes a scientific contribution by strengthening the conceptual framework for harmonizing the two legal systems in the resolution of inheritance disputes and recommends strengthening regulations to enhance the effectiveness and legal certainty of APS. This study is limited to a literature-based normative review and therefore does not examine implementation through an analysis of court decisions.